Teams Games Tournament (TGT): memadukan unsur competitive dan cooperative dalam rangka peningkatan kualitas pembelajaran PKn - Suyato Suyato (Universitas Negeri Yogyakarta, 2006)
Many researches has been done in searching the advantages and disadvantages, both Cooperative and Competitive model of teaching, each of them has marry advantages. Accordingly, the rest task of teachers is to take the advantages and eliminate its disadvantages. This article tries to propose Team Game Tournament as a means in integrating cooperative and competitive aspects of instructional activity. With its distinctive feature, TGT can combines both cooperative and competitive spirits of student as a result, hopefully, student' achievement will increase. Implementation of TGT in some right occasion is one of means in increasing instructional effectiveness.